Analysis of the Implementation of Angklung Art Learning Patterns as Early Childhood Actualization - Joko Pamungkas Lecturer; Ad Dieni Maulana Rizka (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Learning for early childhood aims to develop various abilities and train children in meeting their needs. One of the needs of children is self-actualization which can be stimulated through learning at school. Learning activities at school can be done with various activities. One of them is angklung learning activities. Where these activities are extracurricular activities at school with the aim of increasing children's talents and interests. This study aims to determine how to implement angklung learning patterns in schools as a form of early childhood actualization. This research was conducted with qualitative descriptive research methods with data collection through observation, interviews, and documentation. The results of this research were analyzed to find out what kind of angklung learning can realize early childhood self-actualization.